Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Test - Page 832: 4


$x_{1}=3+ \sqrt{7}$ and $x_{2}=3- \sqrt{7}$

Work Step by Step

Given $u^2-6u+2=0$ $a=1, \ b=-6, \ c=2$ Using the quadratic formula: $\dfrac{-b\pm \sqrt{b^2-4ac}}{2a} , $ we have: $\dfrac{-(-6)\pm \sqrt{(-6)^2-4\times 1\times 2}}{2\times 1} = \dfrac{6\pm \sqrt{36-8}}{2} = \dfrac{6\pm \sqrt{28}}{2} = \dfrac{6\pm \sqrt{4\times 7}}{2} = \dfrac{6\pm 2\sqrt{7}}{2} = 3\pm \sqrt{7}$ Therefore the solutions are $x_{1}=3+ \sqrt{7}$ and $x_{2}=3- \sqrt{7}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.